Rietveld refinements of SnO(2) ceramic powders doped with ZnO, WO(3), CoO, Nb(2)O(5) and MoO(3) - Carrio, J. A. G.; Masson, T. J.; Munhoz, A. H.; de Jesus, M. M. [UNESP]; Perazolli, L. [UNESP]; Coleto, U. [UNESP]; Gutierrez-Antonio, S. [UNESP]; Marques, Rodrigo Fernando Costa [UNESP]; Paiva-Santos, C. O. [UNESP] (Oldenbourg Verlag, 2007)
Polycrystalline materials of SnO(2) doped with ZnO, WO(3), CoO, Nb(2)O(5), and MoO(3). were synthesized by solid state reaction. X-ray powder diffraction data were collected with Cu K(alpha) radiation from a Rigaku-Rint 2000 rotating anode source. The structural and profile parameters were refined by the Rietveld method using GSAS [2]. The obtained residual parameters are R(wp) = 11,93% and R(Bragg) = 4,19%. The refined profile parameters indicate no anisotropic crystallite microstrain. The refinement results and Fourier differences calculations indicate that the dopants do not occupy interstitial sites in the crystal structure of SnO(2).
Keywords: SnO(2); varistor; Rietveld